The case for routine HIV screening and impact of managed care. - Sullivan, Lynn E; Fiellin, David A (The American journal of managed care, 2010)
An estimated 230,000 people in the United States are unaware that they are infected with the human immunodeficiency virus (HIV). Targeted testing strategies are likely to miss a significant proportion of the HIV-infected population, and routine screening could help identify individuals who are likely to experience complications or transmit the virus. Recent advances in treatment, including the introduction of highly active antiretroviral therapy, have dramatically extended the life expectancy of HIV-infected individuals and allowed many patients to have their condition managed in a manner similar to other chronic diseases. There are no quality of care measures, such as Healthcare Effectiveness Data and Information Set (HEDIS) measures, that pertain to routine HIV screening in managed care. Such measures may improve the identification of patients with HIV, and bring them into care earlier. Routine screening would provide the opportunity to identify more HIV-infected persons and bring them into care, a process that would be cost-effective in the long term. Early detection allows for the timely provision of antiretroviral medications, immunizations, and prophylactic antimicrobials, which substantially reduces mortality and hospitalizations. Given the public health impact of HIV infection, federal and private partnerships should be considered to establish routine HIV screening practices.
Keywords: Anti-HIV Agents; Cost-Benefit Analysis; Counseling; HIV Infections; Humans; Managed Care Programs; Mass Screening; Medication Adherence; Patient Acceptance of Health Care; Practice Guidelines as Topic